Interconnected Na2Ti3O7 nanotube/g-C3N4/graphene network as high performance anode materials for sodium storage. (31st July 2020) - Wang, Shuaihao; Zhu, Yuanyi; Jiang, Meng; Cui, Jinlong; Zhang, Yongqiang; He, Wenxiu
Abstract: The high-performance anode electrode material has been the major challenge of sodium ion batteries (SIBs). In this paper, we report a facile strategy to fabricate three-dimensional (3D) network structures where Na2 Ti3 O7 nanotube species are anchored to the composites composed of graphite phase carbon nitride (g-C3 N4 ) and ultrafine graphene, and demonstrates the excellent electrochemical performance as a sodium storage material. The good integration of g-C3 N4 and graphene provides more active sites for Na + insertion/extraction and accommodates the volume expansion of Na2 Ti3 O7 . The Na2 Ti3 O7 nanotube into these carbon matrix can effectively shorten the transport paths of Na + . Therefore, the Na2 Ti3 O7 NT/g-C3 N4 /RGO electrode exhibits a superior cycling efficiency and rate capability. When used as the anode material of sodium half-cell, the reversible capacity of the synthesized Na2 Ti3 O7 NT/g-C3 N4 /RGO composite is as high as 210.8 mAh g −1 after 300 cycles at 0.1 A g −1 and good rate capability (104.7 mAh g −1 at 2 A g −1 ). After the 50 cycle, the corresponding coulomb efficiency remained basically stable and is up to 98%. In addition, the half-cell provides high energy density of 364 Wh kg −1 at power density of 0.048 W kg −1 . Highlights: Na2 Ti3 O7 NT/g-C3 N4 /RGO Network is prepared by alkaline hydrothermal. The sample retains a capacity of 210.8 mAh g −1 after 300 cycles at 0.1 A g −1 . The g-C3 N4 /RGO support causes a better cycling performance for sodium storage.